Territorial dynamics and local knowledge around conflicts in a neighborhood in Nova Friburgo (RJ) after the 2011 disaster: Territorial dynamics and local knowledge around conflicts in a neighborhood in Nova Friburgo (RJ) after the 2011 disaster - Timoteo Correa, Maria Suellen (Argumentos - Revista do Departamento de Ciências Sociais da Unimontes, 2020)
This article analyses the ways in which social and political participation for the reconstruction of spaces affected by rain catastrophes can reverberate in the relation of the Public Power with communities and the urban public policies. The intention is to present the local knowledge in territorial disputes and in the access to technical spaces and public policies for disaster management and urban planning – so part of my masters research is presented, involving the case study of the political participation of residents of Córrego D'Antas neighborhood, in Nova Friburgo (RJ), in favor of the locality reconstruction and the services improvements, after being hit by the disaster involving rainfall, floods and landslides in 2011. Some cases will be addressed, as works and review meetings with City Hall in the neighborhood in 2014. The participation through the residents association in the neighborhood and the activation of new knowledges in the political sphere are taken as examples in this article, in order to bring reflections on the affirmation of territorialities in urban disaster contexts.